Pengaruh Kemiskinan, Pendapatan Dan Pendidikan Terhadap Tingkat Konsumsi Rokok (Studi Kasus 34 Provinsi Di Indonesia Tahun 2020-2024) - Izam Zamali (CV. SINAR HOWUHOWU, 2026)
Cigarette consumption in Indonesia is still a significant problem, especially among communities with diverse socioeconomic levels. Cigarettes not only have an impact on health, but also cause an economic burden on households, especially on the poor. This study aims to analyze the influence of the variables of Poverty, Income, and Education on the Level of Cigarette Consumption in 34 provinces in Indonesia during the period 2020-2024. This study uses a quantitative method with a panel data approach (cross-section of 34 provinces and time-series for 5 years). The analysis technique used is panel data regression analysis with the random effect model. Tests were conducted through the t test (partial), F test (simultaneous), and the test of the coefficient of determination (Adjusted R-squared). The results showed that partially, the poverty variable had a negative and insignificant effect on the level of cigarette consumption. The income variable has a positive and significant effect on the level of cigarette consumption. Meanwhile, the education variable has a negative and significant effect on the level of cigarette consumption. Simultaneously, poverty, income, and education have a positive and significant effect on the level of cigarette consumption in Indonesia. The Adjusted R-squared value of 0.222747 indicates that the three variables are able to explain the variation in cigarette consumption by 22.27 percent, while the rest is influenced by the faculty of education.